Photobiomodulation therapy for congenital color vision deficiency: results of a preliminary randomized clinical trial - Liu, Yidi; Yang, Qinghua; Yu, Jun; Jia, Liang (Frontiers in Medicine, 2024)
PurposeThis study presents a novel randomized controlled trial investigating photobiomodulation (PBM) therapy as an intervention method for color vision deficiency (CVD).MethodsA total of 74 participants with CVD were assigned to either the PBM group or the control group. In the PBM group, participants wore virtual reality (VR) goggles twice daily, with a 12-h interval, over a four-week period. The VR video consisted of alternating red and green images, each presented for 5 s, totaling 6 min and 20 s. No treatment was administered to the control group. Color vision improvement was assessed using Yu’s, Ishihara’s pseudoachromatic plates, Color Blindness Check (CBC), and FM-100 Hue total error score (TES).ResultsAfter 4 weeks, in terms of Yu’s and Ishihara’s Plates, the patients in PBM group could identify increasing pieces (before: 1.6 ± 1.6, 2.3 ± 2.2; 4 weeks: 6.5 ± 4.4, 5.4 ± 2.9), while in control group, the number was before: 2.6 ± 3.4, 2.6 ± 2.5; 4 weeks: 3.3 ± 3.6, 2.9 ± 2.2. As for CBC scores, the patients in PBM also showed improved high scores (before: 2353.3 ± 700.0; 4 weeks: 2693.6 ± 642.5). Moreover, PBM treatment resulted in a significant reduction of FM-100 scores (before: 298.0 ± 211.3; 4 weeks: 202.1 ± 114.4).ConclusionThese findings suggest that PBM therapy holds promise as a potential treatment option for individuals with CVD.Clinical trial registrationThe study received approval from the Ethics Committee of PLA General Hospital, China (KY2021-017). Additionally, it was registered as a Chinese domestic clinical trial (ChiCTR2200056761) at “http://Chictr.org.cn/index.aspx”.